Exploring the role of nurses as 'intermediaries' in bridging the gap between biomedical and lay knowledge of disease : a case study of malaria and HIV/AIDS in Kisumu, Kenya. - Sadruddin, Aalyia (My University, 2011)
“Health”, “Illness” and “Disease” are multifaceted concepts and are perceived in a range of ways by different health care professionals. This study, using qualitative research, aims to understand nurses pre-existing and current perceptions of malaria and HIV/ AIDS two of Kenya‟s most challenging public health problems. The study recognises that disease categories, beliefs attached to disease and explanations behind methods of help seeking behaviour as understood by nurses, originate from specific socio-historical, cultural and professional experiences. These experiences helped nurse‟s traverse between meanings attached to the allopathic (biomedical), popular and traditional health care models and create a unique space in which a myriad of meanings can be used in line with each other, an outcome that can further inform local health practice. Though malaria and HIV/ AIDS were described within a biomedical framework by nurses, they understood that patients attached multiple meanings to the aetiologies and treatments of both diseases. Nurses stood as key informers for medical doctors and encouraged them to take cognisance of patients‟ views- a difficult task. In doing so, nurses showed their ability to sensitively integrate non-biomedical and biomedical causalities in their everyday clinical encounters. Speaking in local dialects and reflecting on their views of disease before and after their professional training showed nurses as engaging in processes of “cultural mediation” and “cultural brokering”, two crucial aspects of their professional role. This study indicates the importance of documenting nurse‟s knowledge in representing local biomedical and non-biomedical views of disease so as to better adapt health messages in such contexts.